Predictive Capacity for Perceived Self-Efficacy Trends towards Inclusive Education Practices of Pre-Service Teachers - Muhaidat, Muhammad; Falah , Al-Hanouf (Dirasat: Educational Sciences, 2023)
Objectives: The study aimed to explore the predictive capacity of self-perceived competence in pre-service teachers' attitudes towards inclusive education practices. Methods: The predictive descriptive approach was employed using the Self-Perceived Competence Scale and the Attitudes towards Inclusion of Students with Disabilities Scale. The study sample consisted of 275 pre-service students in special education selected purposively from the field training students in the academic year 2021/2020. Results: The overall results of the Self-Perceived Competence Scale indicated no statistically significant differences (α=0.05) among the sample participants regarding gender, educational level, training programs, interaction experience, cumulative GPA, and university. However, there was a significant effect of gender and university on the computational means of self-perceived competence dimensions. Lastly, the results revealed a statistically significant predictive relationship between self-perceived competence and attitudes towards inclusive education practices. Conclusions: The study recommended conducting further research to review pre-service teacher preparation programs and develop a set of quality training programs to enhance teachers' competencies in inclusive practices.